Intranasal oxytocin modulates higher order social cognition in body dysmorphic disorder. Issue 2 (7th January 2019) - Fang, Angela; Lawson, Elizabeth A.; Wilhelm, Sabine
Abstract : Background: Body dysmorphic disorder (BDD) is a psychiatric disorder with specific impairments in social cognition related to excessive concerns about one's appearance. Individuals with BDD have difficulty identifying emotional expressions and attribute internal factors for others' emotional expressions in self‐referent (but not other‐referent) scenarios. Given the role of oxytocin in regulating social approach behavior and social salience, we hypothesized that oxytocin would improve biases in emotion recognition, attributions, and threat interpretations in individuals with BDD, compared to healthy controls (HCs). This is the first study to examine the effects of oxytocin in people with BDD. Methods: Eighteen participants with BDD and 16 HCs received a single dose of 24 international units of intranasal oxytocin (Syntocinon®) or matching placebo in a randomized, placebo‐controlled, within‐subject crossover design. Participants completed the Emotion Recognition Task and Interpretation Questionnaire 45 min after administration. Results: Oxytocin, relative to placebo, did not improve emotion recognition accuracy in either self‐referent or other‐referent contexts for individuals with BDD. However, oxytocin led to greater internal attributions in other‐referent contexts for those with BDD compared to HCs. Rather than reducing self‐blame, oxytocin led to other‐directed blame. Oxytocin did not impact threat interpretations in BDD. Conclusions: Oxytocin may only impact specific aspects of higher order social cognition in BDD and may have unwanted effects on emotion attributions. Our results caution its clinical use in BDD.